A study on occupational health and safety - Lídia Maria Costa Araújo Magalhães; Ketyllem Tayanne da Silva Costa; Gustavo Nepomuceno Capistrano; Maryanna Damasceno Leal; Fábia Barbosa de Andrade (BMC, 2022)
Abstract Background This study aimed to evaluate and describe the indicators of occupational health, with a focus on the medical expertise and periodic medical examination. Methods This is exploratory-descriptive, cross-sectional, documentary, quantitative, and retrospective research, in the historical series: 2011 to 2015. Results The number of lost days of work per worker and the frequency of licenses increased despite the decrease in the Absenteeism Duration Index and stabilization of the Frequency of Medical Workers. As for the adhesion of the workers to the Periodic Medical Examinations, it was decreasing, with a higher percentage in the year 2012 (35.3%). During the analyzed period, 5,186 workers performed the Periodic Medical Examination, and the majority (60.6%) presented non-ideal weight, 41.1% were sedentary, 33.2% had dyslipidemia, 29.0% were alcoholic, 3.2% were smokers, 5.9% had diabetics, and 16.4% reported high noise in the workplace, 27.8% inadequate lighting and 35.9% inadequate work furniture. Conclusions The results highlight the need to maintain and strengthen the Worker Health and Safety Policy with emphasis on surveillance, aiming at the promotion and protection of the health of the workers, based on the elaboration of the epidemiological profile of health and, consequently, the implementation of positive impact strategies.